Revealing the Foggara as a Living Irrigation System through an Institutional Analysis: Evidence from Oases in the Algerian Sahara. Issue 1 (22nd December 2021) - Idda, Salem; Bonté, Bruno; Kuper, Marcel; Mansour, Hamidi
The foggara in the Algerian Sahara has often been portrayed as a traditional ingenious but immutable irrigation system incapable of keeping up with the radical socioeconomic and environmental transformations of the 20 th and 21 st centuries. Yet, oasis populations continue to use a large number of foggaras. The aim of this study was to reveal the importance of institutions in adapting and preserving the living character of foggaras. Adapting the physical infrastructure and the institutions governing the use of contemporary foggaras are key to adapt to change, weaving different threads of tradition and modernity to maintain collective action and keep the foggaras flowing. We show that Ostrom's design principles are not only an interesting lens to explore the durability of long-standing self-governing irrigation systems, but also, when these principles are challenged, to characterize transformations of the foggara at a time of contested change.